2017
DOI: 10.1038/ncomms15369
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming the crystallization and designability issues in the ultrastable zirconium phosphonate framework system

Abstract: Metal-organic frameworks (MOFs) based on zirconium phosphonates exhibit superior chemical stability suitable for applications under harsh conditions. These compounds mostly exist as poorly crystallized precipitates, and precise structural information has therefore remained elusive. Furthermore, a zero-dimensional zirconium phosphonate cluster acting as secondary building unit has been lacking, leading to poor designability in this system. Herein, we overcome these challenges and obtain single crystals of three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
189
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 410 publications
(193 citation statements)
references
References 85 publications
3
189
0
1
Order By: Relevance
“…The novel sorbent was successfully used for the d-SPE of uranyl ions prior to its determination by ICP-MS. Uranium uptake by MOFs has been also studied by Zheng et al [95]. Uptake of strontium and technetium with metal-organic frameworks has been also reported [96,97].…”
Section: Extraction Of Uraniummentioning
confidence: 92%
“…The novel sorbent was successfully used for the d-SPE of uranyl ions prior to its determination by ICP-MS. Uranium uptake by MOFs has been also studied by Zheng et al [95]. Uptake of strontium and technetium with metal-organic frameworks has been also reported [96,97].…”
Section: Extraction Of Uraniummentioning
confidence: 92%
“…Among them, tritopic linkers have been particularly investigated by several groups, and a recent review on the topic has been published, to which the interested reader is directed [73]. Besides tritopic linkers, tetratopic ones with either tetrahedral or square geometry have also proved successful in generating open framework compounds [74][75][76][77]. A notable example is the linker Ni-tetrakis(4-phosphonophenyl)porphyrin, which was combined with both divalent metals, namely, Mn, Co, Ni, and Cd [46,78], and tetravalent metals, namely Zr and Hf [47], to produce permanently porous compounds, termed CAU-29, CAU-36, and CAU-30, respectively (Figure 14a,b).…”
Section: Porous Materialsmentioning
confidence: 99%
“…It has been reported that the MOFs constructed from trivalent or tetravalent metal ions and oxygen‐containing ligands show higher chemical and water stability , . For example, Wang's group demonstrated that the highly crystalline 3D zirconium(IV) phosphonate MOFs displaying a superior stability in acidic solutions for capture of UO 2 2+ . In addition, MOFs based on special structural motifs also exhibit high water stability such as the series of MOF‐74 featuring one‐dimensional (1D) rod‐shaped metal‐carboxylate secondary building units (SBUs) , .…”
Section: Introductionmentioning
confidence: 99%